2017
DOI: 10.4049/jimmunol.1602072
|View full text |Cite
|
Sign up to set email alerts
|

The Induction of Pro–IL-1β by Lipopolysaccharide Requires Endogenous Prostaglandin E2 Production

Abstract: PGE has been shown to increase the transcription of pro-IL-1β. However, recently it has been demonstrated that PGE can block the maturation of IL-1β by inhibiting the NLRP3 inflammasome in macrophages. These apparently conflicting results have led us to reexamine the effect of PGE on IL-1β production. We have found that in murine bone marrow-derived macrophages, PGE via the cAMP/protein kinase A pathway is potently inducing IL-1β transcription, as well as boosting the ability of LPS to induce IL-1β mRNA and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 28 publications
2
81
0
Order By: Relevance
“…has recently been shown to play an important role as a necessary autocrine stimulant for the production of pro-IL-1β by LPS-stimulated macrophages (discussed further below). 18 We found that the PPP plays an important role in these processes by supporting the production of NADPH, an important cofactor for FAS ( Figure 1). In addition, the PPP generates ribose for nucleotide synthesis (Figure 1), which is critical for DNA and RNA synthesis with the latter presumably being important in the strong transcriptional response that results from TLR engagement.…”
Section: This Correlatesmentioning
confidence: 82%
“…has recently been shown to play an important role as a necessary autocrine stimulant for the production of pro-IL-1β by LPS-stimulated macrophages (discussed further below). 18 We found that the PPP plays an important role in these processes by supporting the production of NADPH, an important cofactor for FAS ( Figure 1). In addition, the PPP generates ribose for nucleotide synthesis (Figure 1), which is critical for DNA and RNA synthesis with the latter presumably being important in the strong transcriptional response that results from TLR engagement.…”
Section: This Correlatesmentioning
confidence: 82%
“…In a more recent study in murine macrophages, PGE 2 has been identified to promote pro‐IL‐1β processing. PGE 2 can signal through the EP2 receptor, and ablation of the EP2 receptor decreases IL‐1β maturation in an NLRP3‐dependent manner . Furthermore, in primary human monocytes, PGE 2 was shown to boost processing of pro‐IL‐1β by NLRP3.…”
Section: Lipid Metabolism and Nlrp3 Functionmentioning
confidence: 99%
“…PGE 2 can signal through the EP2 receptor, and ablation of the EP2 receptor decreases IL-1β maturation in an NLRP3-dependent manner. 60 Furthermore, in primary human monocytes, PGE 2 was shown to boost processing of pro-IL-1β by NLRP3. The role of PGE 2 -mediated PKA activation on NLRP3 activity however, is not fully elucidated.…”
Section: Lipid Metabolism and Nlrp3 Functionmentioning
confidence: 99%
“…Eicosanoids, including prostaglandins (PGs) and leukotrienes, are derived from AA via the COX and 5‐LOX pathways, respectively . PGE 2 , an abundant eicosanoid present in LPS‐induced BMDMs owing to COX‐2 activation and 15‐hydroxydehydrogenase inhibition, is required for IL‐1 β transcription through interaction with the EP2 receptor, which leads to increased cAMP signalling . It is noteworthy that in macrophages, exogenous PGE 2 added after LPS negatively regulates NLRP3 inflammasome activation, whereas PGE 2 added before LPS promotes this process .…”
Section: Metabolic Reprogramming Controls Inflammasome Activationmentioning
confidence: 99%
“…PGE 2 , an abundant eicosanoid present in LPS‐induced BMDMs owing to COX‐2 activation and 15‐hydroxydehydrogenase inhibition, is required for IL‐1 β transcription through interaction with the EP2 receptor, which leads to increased cAMP signalling . It is noteworthy that in macrophages, exogenous PGE 2 added after LPS negatively regulates NLRP3 inflammasome activation, whereas PGE 2 added before LPS promotes this process . Additionally, a rapid increase in eicosanoids, termed an ‘eicosanoid storm’, is detected during NAIP5/NLRC4 inflammasome activation, which facilitates the recruitment of neutrophils to clear pathogens after pore‐induced intracellular traps are formed following pyroptosis …”
Section: Metabolic Reprogramming Controls Inflammasome Activationmentioning
confidence: 99%